2021
DOI: 10.3390/jcm10235693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-Existing Placental Pathologies in Pregnancies Complicated by Placental Abruption and Acute Neonatal Outcomes

Abstract: Placental abruption (PA) is a concern for maternal and neonatal morbidity. Adverse neonatal outcomes in the setting of PA include higher risk of prematurity. Placental pathologies include maternal vascular malperfusion (MVM), fetal vascular malperfusion (FVM), acute chorioamnionitis, and villitis of unknown etiology (VUE). We aimed to investigate how placental pathology contributes to acute neonatal outcome in PA. A retrospective cohort study of all placentas with PA were identified. Exposures were MVM, FVM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…These could lead to clinical preeclampsia, preterm birth, fetal demise and fetal growth restriction [ 8 ]. Furthermore, placental pathology was associated with more severe neonatal outcomes, with a higher rate of admission to the NICU [ 31 ]. Nevertheless, a recent meta-analysis of 30 studies concluded that the incidence of vascular and inflammatory lesions was comparable to that of non-COVID-19 pregnancies, and there was no specific lesion associated with COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These could lead to clinical preeclampsia, preterm birth, fetal demise and fetal growth restriction [ 8 ]. Furthermore, placental pathology was associated with more severe neonatal outcomes, with a higher rate of admission to the NICU [ 31 ]. Nevertheless, a recent meta-analysis of 30 studies concluded that the incidence of vascular and inflammatory lesions was comparable to that of non-COVID-19 pregnancies, and there was no specific lesion associated with COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women who had more severe placental lesions of maternal vascular malperfusion after preeclampsia had a three-fold increased risk of screening as high-risk for CVD compared to women without these lesions [ 3 ]. Interestingly, fetal health can also be investigated through placental pathology, where the odds of neonatal intensive care unit (NICU) admission were twice as high in pregnancies with placental pathologies in addition to placental abruption [ 4 ]. Furthermore, inflammation in the extra-placental membranes showed that the inflammatory milieu of amniotic fluid increases with chorio-deciduitis grade, but not amnionitis of these membranes [ 5 ].…”
mentioning
confidence: 99%